EXPERIMENTAL EVALUATION OF LOW ENERGY BUILDING USING DOUBLE-SKIN GREEN FAÇADE IN TROPICAL CLIMATE - KOH , KELLY (2020)
As people are spending most of their time indoors, the building sector has been dominating the total energy consumption due to the utilization of air-conditioning and mechanical ventilation to provide a comfortable indoor working environment. This research work aims to achieve a low energy building with a passive approach, focusing on the building envelope considering thermal performance, energy saving, cost-benefit analysis and thermal comfort. That has been achieved by installation of double-skin green façade on the post-graduate office building located in the solar research site in Universiti Teknologi PETRONAS with geographical coordinates of 4.3838˚N, 100.9709˚ E.